The Impact of Family Socioeconomic Status on Parental Involvement in Children's Education: Differences between High- and Low-SES Families in Indonesia - Mas'ud, Bulqia; Imansari, Nurul; Sunusi, Zulfianah; Saiful, Sri Hastuti Novila Anggraini (Universitas Ahmad Dahlan, 2025)
This study explores how family socioeconomic status (SES) affects parental involvement in children's education in Indonesia, specifically within home and school environments. Although parental involvement is essential for academic success, differences across SES groups in Indonesia are not yet fully understood. Using data from 160 families representing diverse SES backgrounds, this research employed t-tests and correlational analyses to examine the influence of SES on parental involvement. Results show that families with higher SES exhibit greater involvement in home-based educational activities, while involvement at school remains consistent across different SES levels. Additionally, notable gender differences emerged: mothers from high-SES families were significantly more involved compared to mothers from low-SES families, whereas fathers' involvement did not significantly differ based on SES. Correlational analyses further demonstrated that SES indicators, particularly parental education levels, were strongly associated with home-based involvement but had little relation to school-based involvement. Regression analysis confirmed that SES significantly predicts home involvement but not involvement at school. These findings underscore the importance of providing targeted support to promote home-based parental involvement among low-SES families. Future research should investigate qualitative factors, such as school policies and cultural norms, to better understand their impact on parental involvement.